Potensi Cadangan Biji Tumbuhan Bawah Pasca Erupsi Merapi di Taman Nasional Gunung Merapi: Seed Bank Potential of Understorey Plants After The Eruption of Merapi Volcano in Mount Merapi National Park - Fadilah, Anisa; Sulistijorini; Ariyanti, Nunik Sri (Departemen Biologi, Institut Pertanian Bogor, 2024)
The 2010 eruption of Mount Merapi caused the ecosystem of Mount Merapi National Park had damage. The recovery of the surrounding ecosystem was called succession . Soil seed bank can be a seed resource for the succession. This research was conducted to analyze vegetation composition and explore the potential seed bank of understorey plants. The vegetation analysis was done using a quadratic method in the three locations: highly damaged, moderately damaged, and lightly damaged. A 1×1 m2 plot was used to collect 9 soil samples from each location. The soil samples were stored in a greenhouse for the germination test. Results showed that Poaceae dominated the vegetation in three locations. The vegetation in moderately and lightly damaged locations has a higher score in diversity and evenness than that in highly damaged locations. The seed bank results showed approximately 34 understorey plants from 14 families dominated by Poaceae. The similarity between the standing aboveground vegetation and soil seed banks in the three locations was low.